Using Moringa oleifera Lamarck seed extract for controlling microbial contamination when producing organic cachaça - Teixeira, Vitor [UNESP]; Silva, Aline Ferreira [UNESP]; de Freita, Cristhyane Millena [UNESP]; de Freita, Lidyane Aline [UNESP]; Mendes, Franciele Quintino [UNESP]; Tralli, Letícia Fernanda [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (Elsevier, 2019)
This study investigated the use of seed extract from Moringa oleifera Lamark (MO) for both clarifying the sugarcane juice and removing fermentation contaminants that originated during the 24 h storage of the freshly cut stalks. The addition of the MO seed extract during the juice clarification step decreased the total microbial population by 41.66% compared to the other treatments. The non-stored raw material had less lactic acid bacteria and yeasts counts in the fermentation process, resulting in 8.8% lower glycerol content compared to the stored raw material. The concentrations of congeners in both raw materials decreased by 5.27% after liming and by 10% after using the natural extract with flocculation activity. It can be concluded that the clarification process combined with the use of the seed extract from Moringa oleifera Lamarck can potentially control microbial contaminating during fermentation and increase the alcohol content in the cachaça.
Keywords: Brandy; Clarification; Feedstock; Saccharomyces cerevisiae; Sugarcane